Endogenous endophthalmitis due to Salmonella choleraesuis in an HIV-positive patient - Rapeeporn Yodprom (2018)
Purpose: To report a case of endogenous endophthalmitis caused by the gram-negative bacterium Salmonella choleraesuis as a first sign of HIV infection in a patient from Thailand. Method: Case description and literature review. Results: A 54-year-old male without systemic complaints developed non-painful panuveitis in his left eye accompanied by high intraocular pressure. On investigation, HIV serology was found positive, and aqueous and blood cultures revealed the bacterium Salmonella choleraesuis. Despite aggressive treatment with antibiotics, the affected eye did not improve, and his visual acuity decreased to no light perception. Conclusions: Endogenous endophthalmitis with the non-typhoidal Salmonellae can occur in the absence of systemic symptoms in an immunocompromised host. Copyright © Informa Healthcare.